Corepressor for element-1–silencing transcription factor preferentially mediates gene networks underlying neural stem cell fate decisions - Abrajano, Joseph J. (National Academy of Sciences, 2010)
The repressor element-1 (RE1) silencing transcription factor/neuron-restrictive silencer factor (REST/NRSF) silences neuronal genes in neural stem cells (NSCs) and nonneuronal cells through its role as a dynamic modular platform for recruitment of transcriptional and epigenetic regulatory cofactors to RE1-containing promoters. In embryonic stem cells, the REST regulatory network is highly integrated with the transcriptional circuitry governing self-renewal and pluripotency, although its exact functional role is unclear. The C-terminal cofactor for REST, CoREST, also acts as a modular scaffold, but its cell type-specific roles have not been elucidated. We used chromatin immunoprecipitation-on-chip to examine CoREST and REST binding sites in NSCs and their proximate progenitor species. In NSCs, we identified a larger number of CoREST (1,820) compared with REST (322) target genes. The majority of these CoREST targets do not contain known RE1 motifs. Notably, these CoREST target genes do play important roles in pluripotency networks, in modulating NSC identity and fate decisions and in epigenetic processes previously associated with both REST and CoREST. Moreover, we found that NSC-mediated developmental transitions were associated primarily with liberation of CoREST from promoters with transcriptional repression favored in less lineage-restricted radial glia and transcriptional activation favored in more lineage-restricted neuronal-oligodendrocyte precursors. Clonal NSC REST and CoREST gene manipulation paradigms further revealed that CoREST has largely independent and previously uncharacterized roles in promoting NSC multilineage potential and modulating early neural fate decisions.